Butchery activities associated with Member 5 at Sterkfontein, South Africa - (:unkn) unknown (My University, 2025)
The origin of animal tissue consumption within the hominin lineage remains a central question in palaeoanthropology and taphonomy. This question is mostly addressed through the study of bone surface modifications (e.g., butchery marks) observed on fossils from East African sites. Albeit somewhat overlooked compared to East Africa, South Africa provides an additional body of evidence regarding the evolution of hominin behaviours. Here, we provide a comprehensive description and analysis of a butchered bone assemblage from the Sterkfontein Name Chamber and Member 5 East Oldowan infill in South Africa, dated conservatively to between 1.4 and 2.18 Ma. Based on the anatomical location and morphology of the bone surface modifications, we demonstrate that hominins using Oldowan tools were capable of performing a complete butchery sequence that included skinning, disarticulation, defleshing and marrow extraction. Furthermore, comparison with the butchered bones from the neighbouring sites of Cooper’s D and Swartkrans shows a continuity, or the repeated emergence, of similar butchery patterns through the Early Pleistocene. The identification of distinct butchery patterns, the range of exploited animals, as well as the presence of bone tools in many sites highlight the diversity of hominin subsistence behaviours during the Early Pleistocene, which we interpret as a reflection of the likely non-linear evolution of such behaviours. Finally, we argue that the research focus of taphonomic analyses should address how hominins processed carcasses in addition to how and when these were acquired. Such analyses would help identifying the development of complex butchery practices in the archaeological record.
Keywords: African Research